1996
DOI: 10.1093/oxfordjournals.humrep.a019438
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome and follow-up of 82 children aged 1-9 years old conceived from cryopreserved embryos

Abstract: Embryo cryopreservation is routinely used in in-vitro fertilization (IVF)-embryo transfer programmes. Yet very few studies have reported the follow-up of children conceived with frozen/thawed embryos. This study was designed to follow up the total cohort of children conceived with cryopreserved embryos in A. Béclère Hospital in Clamart, France between 1986 and 1994. We were able to study 89 children, aged 1-9 years old, out of the 93 conceived during this period (lost to follow-up: 4.3%). The prematurity rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 11 publications
2
11
0
2
Order By: Relevance
“…Our findings are reassuring and in line with the recent studies in young IVF children [2,4,7,8,10,11,14,[19][20][21][22][23][24][25] and at primary school age [12,17,18]. Olivennes et al [17] found, in a follow-up study of 422 IVF children aged 6 to 13 years, according to the French school system, that 92.2% of the children had at least average school achievement.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings are reassuring and in line with the recent studies in young IVF children [2,4,7,8,10,11,14,[19][20][21][22][23][24][25] and at primary school age [12,17,18]. Olivennes et al [17] found, in a follow-up study of 422 IVF children aged 6 to 13 years, according to the French school system, that 92.2% of the children had at least average school achievement.…”
Section: Discussionsupporting
confidence: 90%
“…Olivennes et al [17] found, in a follow-up study of 422 IVF children aged 6 to 13 years, according to the French school system, that 92.2% of the children had at least average school achievement. In 1-to 9-year-old IVF children conceived from cryopreserved embryos, the same authors found comparable results for scholastic performance in the school-age children [18]. Levy-Shiff et al [12] examined 9-and 10-year-old IVF children in comparison with naturally conceived children recruited from the IVF children's schools and found that intelligence did not differ between the groups.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Few studies have evaluated the longer-term health effects on children born after frozen embryo transfer [59][60][61][62], with most reporting normal growth and development. In a small, but recent study from New Zealand of 96 term singletons born between 2004 and 2008 and followed up at ages 3.5-11 years, Green et al [62] reported that the transfer of fresh embryos versus frozen embryos was significantly and positively associated with taller stature.…”
Section: Discussionmentioning
confidence: 99%